CONTRIBUTION OF INCOME, EQUITABLE INCOME AND WELFARE OF STREET VENDORS’ FAMILY AT SUNMOR GOR SATRIA MARKET PURWOKERTO BY GENDER - DIJAN RAHAJUNI (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
The existence of the Sunmor GOR Satria market is able to increase economic activity as indicated by the large number of street vendors (pedagang kaki lima/PKL). What motivates the street vendors to run their business is certainly to increase their income to improve their welfare. The more the number of street vendors with identical goods will certainly increase competition among them. This study aims to find out and analyze the contribution of income, distribution of income and welfare of the street vendors as a whole and based on gender. The results of the study state that the overall street vendor income in the Sunmor GOR Satria market contributes to the moderate level of household income, the level of income distribution among the street vendors is in the very uneven category and most of their lives have not been prosperous. Based on gender, the contribution of female street vendors’ income to household income is higher, but the level of income distribution is more uneven compared to male street vendors, and the majority of both of them have not been prosperous. For this reason, it is necessary to improve the management of street vendors, especially in location layout and organization.